2016
DOI: 10.1016/j.jpedsurg.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy in pediatric surgery: Implementation in Canada and supporting evidence

Abstract: In Canada, it has taken a long time to reach high-level implementation of laparoscopic surgery in children. Laparoscopic cholecystectomy first reached plateau, whereas laparoscopic pyloromyotomy continues to increase but remains low despite high level of evidence in support of its usage compared to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Depending on technology of the applied expeditious treatment of cholecystitis patients were divided into two equal clinical groups on number, on 50 people in everyone. At patients of the I clinical group expeditious treatment was carried out by means of laparoscopic technologies through four port, and in II -through uniform access by means of use of a system of access of X-CONE, Karl Storz [2,8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on technology of the applied expeditious treatment of cholecystitis patients were divided into two equal clinical groups on number, on 50 people in everyone. At patients of the I clinical group expeditious treatment was carried out by means of laparoscopic technologies through four port, and in II -through uniform access by means of use of a system of access of X-CONE, Karl Storz [2,8].…”
Section: Methodsmentioning
confidence: 99%
“…In case of inefficiency of medicamentous therapy and in the presence of organic concrements it is expressed reducing «quality of life» of the child expeditious treatment is applied [9]. Today the cholecystectomy at children is carried out mainly with use of laparoscopic technologies [6,10] as their use minimizes decrease «quality of life» of the child and reduces time on necessary by its rehabilitation in the postoperative period in comparison with a classical technique of operation [1,3] To expeditious treatment of children with GD it is applied laparoscopic technologies by means of four port and uniform access [2,8]. In connection with a small amount of clinical observations of performance of a cholecystectomy through uniform access what question from types of laparoscopic technologies of expeditious treatment of children with GD is the least reducing «quality of life» of patients remains open for specialists for today.…”
Section: Relevancementioning
confidence: 99%
“…It also highlights the absence of significant differences between the two techniques. Among the disadvantages, the longer duration and the high cost stand out 6 . Another study points to even higher risk of intraabdominal abscess in laparoscopy 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Sweden denies statistically significant differences between the two techniques regarding surgical wound infection, abscess formation, reoperation and readmission 2 . When choosing the method, the patient's characteristics and the surgeon's experience should be considered 6 .…”
Section: Introductionmentioning
confidence: 99%
“…8 In 2013, Sattarova et al reported that in Canadian pediatric centers, the use of laparoscopy for appendectomy, pyloromyotomy, cholecystectomy, and splenectomy varied greatly (37-90%). 9 A plateau in the use of laparoscopy was reached for cholecystectomy, splenectomy, and appendectomy while despite the high level of evidence, the use of laparoscopic pyloromyotomy remained low but associated with a trend in increasing its implementation (►Fig. 1).…”
Section: Introductionmentioning
confidence: 99%